Measuring the microbiome: perspectives on advances in DNA-based techniques for exploring microbial life - Foster, James A. (Oxford University Press, 2012)
This article reviews recent advances in ‘microbiome studies’: molecular, statistical and graphical techniques to explore and quantify how microbial organisms affect our environments and ourselves given recent increases in sequencing technology. Microbiome studies are moving beyond mere inventories of specific ecosystems to quantifications of community diversity and descriptions of their ecological function. We review the last 24 months of progress in this sort of research, and anticipate where the next 2 years will take us. We hope that bioinformaticians will find this a helpful springboard for new collaborations with microbiologists.